Nanoestruturados lipídicos como estratégia para a utilização tópica de curcumina contra o envelhecimento cutâneo (Revista Brasileira Multidisciplinar, 2022)
The skin is a revealer of healthy aging, in which several resources seek to slow down its senescence and prevent the damage caused by extrinsic factors. Curcumin, the active compound of Curcuma longa L., has been studied as a possible anti-aging adjuvant, due to its functional properties, mainly antioxidant and anti-inflammatory activities. However, its chemical instability and bioavailability make its use difficult. In this context, research has been carried out with the purpose of encapsulating turmeric in nanostructures. The objective of this review is to link the potential of curcumin in the skin aging process to approaches that use nanotechnology, through lipid nanostructures, in order to improve its applicability in topical use. To obtain the data, a qualitative research was carried out through a systematic search using the Google Scholar, Web of Science and Pubmed databases with different combinations of keywords. Despite numerous studies correlating curcumin and nanotechnology, in this work it was possible to observe the scarcity of results that bring the participation of this substance in the aging process, requiring further exploration through research, in view of the great commercial interest of curcumin for rational drug development.